Supportive Psychotherapy for Healthcare Professionals in The Management of Acute Coronary Syndrome: The Use of Delphi Technique - Shatri, Hamzah; Alwi, Idrus; Ismail, Raden Irawati; Herqutanto, Herqutanto; Yuniarti, Kwartarini Wahyu; Soewondo, Pradana; Rengganis, Iris; Harimurti, Kuntjoro; Putranto, Rudi; Abdullah, Vera; Lukman, Petrin R.; Elvira, Sylvia Detri; et al. (Indonesian Society of Internal Medicine, 2022)
Background. Supportive psychotherapy (SP) may increase the benefit of acute coronary syndrome (ACS) management, but there is no structured SP as a guideline for healthcare professionals. This study aimed to develop structured SP as a guideline for implementing psychotherapy in the management of ACS patients in intensive cardiac care unit (ICCU). Methods. This qualitative study used Delphi technique as a modified Delphi method to reach a consensus among experts of structured SP for healthcare professionals in the management of ACS during hospitalized in ICCU. This was developed using self-reflection, observation, and interview of SP implementation in daily psychosomatic practice, gathering literature reviews, doing focus group discussion (FGD) and interview with ACS survivors. During the Delphi rounds, we interviewed 50 informants as source people using valid questionnaires, to proceed a draft of the SP framework and the structured sessions. The SP framework draft and the structured sessions were evaluated and corrected by experts anonymously until the consensus was reached. The validity of the consensus was tested, using Likert psychometric scale to reach an agreement. Cronbach alpha test was used to assess construct validity with SPSS 20. Results. All of preparations conducted before the Delphi rounds showed that ACS patients had psychosomatic disorders during in ICCU, that required support. SP is very helpful to reduce the negative impact of this disorders.Off 50 informants answered a valid and reliable questionnaire which supports the above statement. The draft was made based on the above process. The development of SP for healthcare professionals of ACS managements was reached in a consensus of expert panelists in the second round of the Delphi with Cronbach alpha of 0.9. Conclusion: Supportive psychotherapy (SP) for healthcare professionals in the management of ACS in ICCU were developed and may be applied in clinical practice and research. © 2022, Indonesian Society of Internal Medicine. All rights reserved.